Collaboration or competition? Low-carbon platform regulations and pricing decisions in environmental, social, and governance (ESG) - Kai Cao; Yanlan Mei; Yang Liu (Cleaner Engineering and Technology, 2025)
This study explores the impact of green platform regulatory policies and cooperation strategies within Environmental, Social, and Governance (ESG) on the platform, consumers, and the seller, as well as optimal pricing strategies for the platform and seller. Using game theory, three supply chain models under ESG constraints are examined through numerical simulations. Key findings show that: (1) In Non-cooperation model (Model N), rising consumer environmental awareness (CEA) boosts green sales but reduces platform profits due to high emission costs. (2) In the Non-green Cooperation Model (Model B), stricter platform controls and elevated fines on the seller can lead to reduced prices of non-green products. (3) In the Green Cooperation Model (Model G), a low commission fee can disadvantage the platform. As the seller integrates into the ESG system and the market offers only low-carbon products, competition intensifies between the platform and sellers, potentially decreasing sales. (4) Interestingly, three models have the potential to achieve a triple-win outcome. The platform prefers green cooperative or competitive strategies when ESG investment costs are manageable. Model E extends the analysis with equal platform-seller ESG participation. Numerical analysis confirms the robustness of core profit-commission findings under shared emission-reduction costs, even with parameter variations. This study highlights how different strategies impact competition and cooperation dynamics, providing insights for balancing profitability and social welfare.